High‐Power Multimode Random Fiber Laser for Speckle‐Free Imaging (Ann. Phys. 12/2021). Issue 12 (14th December 2021) - Wang, Shanshan; Zhang, Weili; Yang, Ning; Ma, Rui; Zhang, Yanli; Wang, Zhao; Zhang, Jinchuan; Rao, Yunjiang
Abstract : Random Fiber Lasers A multimode‐fiber‐mediated random fiber laser with 100+ watt output power was demonstrated for speckle‐free imaging, as presented by Shanshan Wang, Weili Zhang, Yunjiang Rao, and co‐workers in article number 2100390 . A random laser combined with multimode fiber provides a powerful platform to realize advanced fiber lasers with controllable spatial characteristics, which is of great significance for applications of imaging and sensing.